Evaluation of the antibacterial and antibiofilm effect of purified dextran from Lactococcus lactis ssp cremoris against some pathogenic bacteria - Istabreq Muhammed Ali Salman; Eman Naji; Jehan Salman; Raghad Aziz (Microbes and Infectious Diseases, 2025)
Background: The development of innovation methods to treat and stop the formation of biofilm has drawn a lot of attention since biofilms are a major health issue due to their multidrug resistance, host defense and other challenges. The goal of our study was to create biopolymer dextran from Lactococcus lactis ssp cremoris and confirm its antimicrobial activity, antibiofilm properties and ability to be included in the preparation of dressings that create an environment that is conductive to wound healing. Methods: The dsrLL gene, which is responsible for dextran production, was examined using an RT-qPCR assay. Sequencing phylogenetic analysis was also achieved. The efficacy of purified dextran was also studied for its antibacterial and antibiofilm activity and in the preparation of wound dressings. Results: The growth reduction of up to 87 % against K. pneumoniae(1), the purified dextran seemed the most effective. For A. baumannii and P.aeruginosa, the anti-biofilm impact of purified dextran reached maximum values of 55 % and 44 %. Additionally , 50  , 46  and 257 %   of the various polymers :  Dextran , PVA  and the combination of Dextran and  PVA , were added and coated the cotton gauze , respectively. Conclusion: Lactococcus lactis ssp cremorisS4 with the highest gene expression level of  dsrLL gene produced dextran. The purified dextran had antibacterial and antibiofilm effect against pathogenic bacteria. Also, dextran can be used in wound dressing, especially with PVA.